Changes in SEP Indicators in Patients using rPMS in Muscle Hypotonia Syndrome - Shamansurov Shaanvar Shamuratovich; N. A. Mirsaidova; D. B. Akhmedjanova (Central Asian Journal of Medical and Natural Science, 2023)
The purpose of the research. Study of changes in somatosensory evoked potensials indicators in patients using repetitive peripheral magnetic stimulation in muscle hypotonia syndrome. In the period of 2022-2023, 110 children of early age (0-3) with muscle hypotonia syndrome were comprehensively examined in the department of "Childhood Nervous Diseases" of the 1st Children’s Clinical Hospital of Tashkent City. In our research, we divided the patients with muscle hypotonia syndrome, that is, the representatives of each group (group 1,2,3,4) into 2 groups. Representatives of the 1st group (47 people): traditional medical treatments, i.e. medical treatment ± rehabilitation. Medicinal treatment includes nootropic, blood circulation improving, acetylcholinesterase drugs and group B vitamins. Representatives of the 2nd group (63 people): rPMS ± rehabilitation. Treatment procedures were continued 10 days every month from 3 to 6 months. Patients underwent SEP examination before and after treatment. In conclusion, rPMS± rehabilitation resulted in a significant and short-term reduction in the latency period of SEP peaks, an increase in the conduction of nerve impulses from the somatosensory pathway in response to stimulation of the n.medianus. Even when rPMS was applied peripherally, significant efficacy was achieved in improving somatosensory cortical conductance in the SEP study of patients with central type of muscle hypotonia syndrome. Our results showed that since rPMS is the hub of spinal cord descending, ascending and segmental nerve signals, non-invasive rPMS has the ability to simultaneously change cortical, corticospinal, spinal cord motor activity and conductance and excitability in peripheral nerves.